Dynamic Characterization of Dendrite Deposition and Growth in Li-Surface by Electrochemical Impedance Spectroscopy. Issue 4 (1st January 2015) - Hernandez-Maya, R.; Rosas, O.; Saunders, J.; Castaneda, H.
Abstract : The evolution of dendrite formation is characterized by DC and AC electrochemical techniques. Interfacial mechanisms for lithium deposition are described and quantified by electrochemical impedance spectroscopy (EIS) between a lithium electrode and a graphite electrode. The initiation and growth of dendrites in the lithium surface due to the cathodic polarization conditions following anodic dissolution emulate long term cycling process occurring in the lithium electrodes. The dendrite initiation at the lithium/organic electrolyte interface is proposed to be performed through a combination of layering and interfacial reactions during different cathodic conditions. The growth is proposed to be performed by surface geometrical deposition. In this work, we use EIS in galvanostatic mode to assess the initiation and growth stages of dendrites by the accumulation of precipitates formed under different current conditions. The lithium/organic solvent experimental system using frequency domain techniques is validated by the theoretical approach using a deterministic model that accounts for the faradaic processes at the interface assuming a coverage fraction of the electrodic surface affected by the dendritic growth.